Single-cell and spatial transcriptome analyses reveal MAZ(+) NPC-like clusters as key role contributing to glioma recurrence and drug resistance - Qiang Gu; Kan Wang; Tingming Lu; Yifei Xiao; Yaqing Wu; Hang Zhou; Kaijia Zhou (Journal of Translational Medicine)
Abstract Background Temozolomide (TMZ) is an important chemotherapeutic agent for glioma treatment. However, the emergence of drug resistance impedes its application. Traditional population-level studies are limited in elucidating resistance mechanisms. Advances in single-cell and spatial transcriptomics technologies provide feasible resolution for studying the cellular composition and dynamics of tumors. In this study, we investigated the heterogeneity of gliomas associated with TMZ resistance at the single-cell and spatial transcriptome levels to identify the resistance mechanisms and potential therapeutic strategies. Methods Single cell sequencing technology was utilized to identify the cellular clusters of gliomas. Drug perturbation analysis and cellular propensity analysis revealed key cluster responding to TMZ. Enrichment analysis was preformed to explore the function of clusters. Transcription factor activity analysis revealed key transcription factors contributing to tumor resistance. Spatial transcriptome data and bulk RNA-seq data validates the role of key transcription factors. Downstream targets of key transcription factors were predicted and validated using gene regulation assays. Drug sensitivity analyses were used to seek viable strategies to overcome drug resistance. Results Glioma cells from before and after temozolomide treatment samples were classified into six clusters: NPC-like cluster, OPC-like cluster, MES-like cluster, AC-like cluster, OC, and Neuron. NPC-like clusters exhibited strong stemness and DNA repair capacity. The activity of MAZ in NPC-like cluster was significantly enhanced after TMZ treatment. The proportion of MAZ( +)_NPC-like cluster was higher in TMZ treated samples. Patients with high proportion of MAZ( +)_NPC-like cluster had poorer survival. Upregulation of MAZ is able to enhance drug resistance in glioma cells, but this phenomenon disappeared when FoxM1 expression was further silenced. The combination of paclitaxel and Trametinib is a promising strategy to overcome resistance. Conclusions NPC-like cluster is prevalent in recurrent and drug-resistant gliomas. MAZ transcription factors are critical regulators that promote the development of drug resistance in NPC-like clusters by enhancing the capacity of DNA repair and stemness. Patients with high proportions of MAZ( +)_NPC-like clusters have poor TMZ sensitivity and prognosis. MAZ enhances stemness and drug resistance in glioma cells by upregulating FOXM1 expression. The combination of paclitaxel and paclitaxel is a promising therapeutic strategy for treating gliomas and overcoming drug resistance.